Analisis SOSTAC dan RACE PLANNING Bagi Industri Pendukung Pariwisata Dalam Menciptakan Keberlanjutan Bisnis. - Salindri, Yerika Ayu; Insanaputra, Yanuar Satrhio; Buchori, Apit; Sulistyo, Agung (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2025)
Digital technology can have a significant impact on business development. The release issued by the Organization for Economic Co-operation and Development (OECD) emphasized that business management needs to adopt and optimize the role of technology. However, many business actors have not integrated technology into their overall business activities. Some of the obstacles include limited knowledge, incompetent human resources, and insufficient financial capabilities. However, business actors who have integrated technology also encounter a range of challenges. Other problems include the effectiveness of digital-based management, the creation of publication content, and the ability to evaluate the strategies used. This study aims to investigate how business actors develop the strategies used. This study employs a qualitative research design. This study focuses on several Yogyakarta SMEs, including OliviaRu, Mahayeri, BoogieStore, Modest-Art, and YAD Blangkon. Among the added values of these businesses are their achievements in business management and their ability to increase sales value by 20% compared to the previous year. Additionally, the traffic generated by digital-based business activities attracts consumers to visit their social media pages. SOSTAC analysis serves as a useful reference and method. We selected this framework due to its conceptual nature, which enables the development of a comprehensive digital-based business management strategy. Through a combination of interview activities and application of concepts, this study produced findings on the implementation of digital-based business management strategies. This study shows that SOSTAC analysis and RACE planning can be one solution. The concept illustrates the strategies and tactics employed. The study's results underscore the need for business actors to undertake a range of steps, including conducting situational analysis, conducting SMART analysis, developing strategies, and refining them through the implementation of tactics.